Predictors predisposing to orocutaneous fistula occurrence following free flap reconstruction - Li, Wenlu; Wu, Shuang; Yuan, Junhui; Meng, Fan; Xu, Chunmiao; Li, Hailiang (Frontiers in Oncology, 2022)
Objectives To explore the possible risk factors of orocutaneous fistula (OCF) development in free flap reconstruction of the tongue/floor of the mouth (TFOM). Methods Data of patients who underwent free flap reconstruction of the TFOM were retrospectively analyzed. The association between clinicopathologic variables and OCF occurrence was analyzed using univariate and multivariate analyses. Results Altogether, 469 patients were enrolled. OCF occurred in 43 patients with a rate of 9.2%. The univariate analysis revealed the negative effects of smoking, preoperative albumin level, cachexia, T4 stage, neck dissection, entire resection of the floor of the mouth (FOM), segmental mandibulectomy, and surgical site infection on OCF occurrence. The multivariate analysis confirmed the independence of cachexia (p<0.001, 4.386[1.883–9.472]), tumor stage (p<0.001, 2.738[1.482–6.629]), entire FOM resection (p<0.001, 6.332[2.110–14.432]), and surgical site infection (p<0.001, 5.376[1.998–11.218]) in affecting the OCF development. Conclusions OCF development following free flap reconstruction of the TFOM was relatively uncommon, but significantly associated with presence of cachexia, T4 stage, entire FOM resection, and surgical site infection.